Social Interaction in the Umrah Pilgrim Registration Process, Ethnomethodology Approach - Yahya, Wardah; Jaharuddin, Jaharuddin (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
This study aims to analyze the dynamics of social interaction between administrative officers and Umrah pilgrims in the registration process, both manually and digitally, using an ethnomethodological approach. This research also explores the social, cultural, and technical factors that influence the quality of interaction in order to understand the formation of social meaning through the actions of indexicality, reflexivity, and contextual action. The research method used is a qualitative approach with descriptive analysis of in-depth interview data and observation of the Umrah registration process. The results showed that social interaction in Umrah registration is a multidimensional phenomenon. The socio-cultural dimension emphasizes the importance of understanding the pilgrims' character, the quality of trust-based social relations, and adaptive communication to the pilgrims' cultural background. The procedural-technical dimension highlights the role of technology in improving service efficiency, despite challenges such as limited digital literacy. The findings show that adaptive communication and religious values are key elements in building harmonious relationships between administrative officers, religious leaders and worshipers. This research provides important implications for strengthening faith-based services through staff training, inclusive technology development, and cultural and religious value-based approaches, which can be applied in local and global contexts.